2019
DOI: 10.3390/met9101063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface and Subsurface Defects on Fatigue Behavior of AlSi10Mg Alloy Processed by Laser Powder Bed Fusion (L-PBF)

Abstract: The fatigue behaviour of an AlSi10Mg alloy processed by laser powder bed fusion (L-PBF) and subjected to different surface finishing processes was investigated paying special attention to the residual defects on the surface and the dominant fatigue failure mechanisms. Roughness measurements and qualitative surface morphology analysis showed smooth surfaces in the case of vibro-finishing and machining followed by polishing. The fatigue performance did not reveal to be directly related to surface roughness, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…The formation of spatter particles ejected from the laser-powder interaction zone, particularly from the melt-pool area, are known to consistently affect the surface properties of the manufactured parts, as well as to generate inner defects in the sub-surface area, which are difficult to remove without properly tuning the post-processing steps [86,[124][125][126][127]. Furthermore, very large spatter particles are most likely to generate lack-of-fusion defects in the final parts since, being potentially bigger (larger diameter) than the layer thickness, the process parameters may be not sufficient to fully melt them, and the spreading of the next powder layer could be inefficient [35].…”
Section: Spattermentioning
confidence: 99%
“…The formation of spatter particles ejected from the laser-powder interaction zone, particularly from the melt-pool area, are known to consistently affect the surface properties of the manufactured parts, as well as to generate inner defects in the sub-surface area, which are difficult to remove without properly tuning the post-processing steps [86,[124][125][126][127]. Furthermore, very large spatter particles are most likely to generate lack-of-fusion defects in the final parts since, being potentially bigger (larger diameter) than the layer thickness, the process parameters may be not sufficient to fully melt them, and the spreading of the next powder layer could be inefficient [35].…”
Section: Spattermentioning
confidence: 99%
“…Towards this aim, a defect-based modelling approach for internal pores has been used with great success [12,14,15]. This was also demonstrated for surface and subsurface pores in [16]. In [15] the authors clearly demonstrated, by the detection through computed tomography (CT) scan of all the defects present in specimens, that the critical defects were the ones with the largest stress intensity factor (SIF), thus supporting the adoption of "extreme value" concepts for estimating the maximum size of defects for fatigue assessment [12] and for comparing the "quality" of different treatments [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray tomography has been used with great success to provide insights into additively manufactured materials, also for viewing of fatigue crack locations [28][29][30]. Recently the detailed analysis of thin struts manufactured in Ti6Al4V combining CT-scan and scanning electron microscopy (SEM) showed that the effect of surface features responsible for fatigue failures could be modelled by Kitagawa-Takahashi diagram [14,16,31]. However, a systematic study about the reasons why failure occurs in some critical surface features and their behaviour for different surface qualities is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of cracks is attributed to the residual stress caused by steep temperature gradients (Gu et al, 2012) (Kaufmann et al, 2016) (Harrison et al, 2015) (Han et al, 2018). Owing to these internal defects, SLM parts exhibit mechanical properties inferior to those of forged parts (Zhang et al, 2017) (Balachandramurthi et al, 2018) (Konečná et al, 2016) (Nasab et al, 2019) (Voisin et al, 2018). Internal defects cause stress concentration (Talemi, 2020) and deteriorate the mechanical properties, especially the fatigue properties, of SLM parts.…”
Section: Introductionmentioning
confidence: 99%